2006
DOI: 10.1099/mic.0.28801-0
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of the immunoglobulin A1 protease gene (iga) from Streptococcus to Gemella haemolysans

Abstract: Bacterial IgA1 proteases share the ability to cleave human IgA1 at the hinge region. Nature has developed this trait along at least five independent evolutionary lineages. To obtain further insight into the phylogeny and function of IgA1 proteases, the nucleotide sequence of the iga gene that encodes the IgA1 protease was determined from two Streptococcus mitis strains and one Gemella haemolysans strain. Heterologous expression in Escherichia coli confirmed that the genes encode human IgA1-cleaving activity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
5
15
0
Order By: Relevance
“…There have been changes in the taxonomic assignment of several mitis group Streptococcus species subsequent to the availability of comparative phylogenetic analyses of core genomes, multilocus sequence analysis (MLSA), and 16S rRNA gene sequence data [23]. In the current study, revised streptococcal taxonomy showed changes in species nomenclature of 25 strains used in phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…There have been changes in the taxonomic assignment of several mitis group Streptococcus species subsequent to the availability of comparative phylogenetic analyses of core genomes, multilocus sequence analysis (MLSA), and 16S rRNA gene sequence data [23]. In the current study, revised streptococcal taxonomy showed changes in species nomenclature of 25 strains used in phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 98%
“…(+) ABP, (-) ABP on bacterial cells (Methods) c S. milleri reclassified as S. anginosis in Ruoff et al [48] d Sabharwal et al [22]; strains sequenced for this study e Brown et al [3] f Strain labeled NCTC 10712 ( S. mitis ) in our collection is now corrected to S. gordonii , UB10712 upon whole genome sequencing g Vorrasi et al [16] h The strain from our collection named S. mitis in Brown et al [3] Submitted to GenBank as S. mitis ; updated to S. oralis in 2015 as per reclassification Takenouchi-Ohkubo et al [28] and Kilian et al [49] i Updated taxonomic classifications for Mitis group, Jensen et al [23] j Reference strains used for genome post-assembly: S. cristatus ATCC 51100 for S. cristatus CC5A and CR3; S. gordonii Challis substrain CH1 for S. gordonii G9B; S. mitis B6 for S. mitis OT25, SK145, SK137; S. parasanguinis ATCC 15912 for S. parasanguinis MGH413; S. salivarius CCHSS3 for S. salivarius KB005…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several bacteria genetically related to these important pathogens produce IgA 1 proteases, reflecting either shared ancestry or, in some cases, horizontal gene transfer. 37,38 The biological significance of IgA 1 proteases is indirectly supported by the fact that they are a striking result of convergent evolution along at least five independent lineages. In spite of virtually identical enzymatic function, IgA 1 proteases of different bacteria belong to all major protease families (i.e., serine proteases, metalloproteases, and thiol proteases).…”
Section: Iga Protease-producing Bacteriamentioning
confidence: 99%